Momias, cráneos y caníbales. Lo indígena en las políticas de “exhibición” del Estado chileno a fines del siglo XIX - Luis Alegría (Centre de Recherches sur les Mondes Américains, 2009)
This paper studies the exhibition of indigenous bodies on Chilean territory in the late-19th century. Based on an understanding of the exhibition as a cultural mechanism and a bio-political exercise of symbolic appropriation, this paper analyses the production of discourse and representation in museums and expositions. The article reconstructs in a historical overview the presence of indigenous bodies in museum exhibitions as well as in cultural events within the country. It identifies the practices of symbolic violence, principally directed by Chilean political institutions in their strategies of national identity-formation.